2015
DOI: 10.1097/qai.0000000000000383
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Bone Mineral Density After 96 Weeks of Treatment With Atazanavir/Ritonavir or Lopinavir/Ritonavir Plus Tenofovir DF/Emtricitabine in Treatment-Naive Patients With HIV-1 Infection

Abstract: : Antiretroviral therapy initiation is associated with declines in bone mineral density (BMD), which seem greatest with tenofovir disoproxil fumarate (DF)-containing regimens. Data comparing protease inhibitors are limited. This CASTLE substudy compared paired baseline with week 96 BMD in patients initiating tenofovir DF/emtricitabine plus atazanavir/ritonavir (n = 106) vs lopinavir/ritonavir (n = 70). In both groups, week 96 BMD declined significantly in arm, leg, trunk, and total body regions. Atazanavir/rit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 35 publications
(44 reference statements)
0
8
0
Order By: Relevance
“…Investigators in the CASTLE substudy reported a greater loss of trunk mean percent BMD in patients on LPV/r compared with those on ATV/r. While no statistically significant difference was seen overall in total body mean percent change between groups, when stratified by sex, greater total body mean percent BMD loss was seen in men on LPV/r compared with men on ATV/r, while no significant difference was seen among women [41*]. Although the evidence regarding the effects of PIs on bone health in treatment experienced patients is less robust, the SPIRAL-LIP study found a 0.01 g/cm 2 increase in the femoral neck BMD of virologically suppressed patients switched from a PI/r-based regimen to a RAL-based regimen, with no statistically significant difference in the total body or total hip BMD [43].…”
Section: The Bone Effects Of the Hiv Protease Inhibitorsmentioning
confidence: 99%
“…Investigators in the CASTLE substudy reported a greater loss of trunk mean percent BMD in patients on LPV/r compared with those on ATV/r. While no statistically significant difference was seen overall in total body mean percent change between groups, when stratified by sex, greater total body mean percent BMD loss was seen in men on LPV/r compared with men on ATV/r, while no significant difference was seen among women [41*]. Although the evidence regarding the effects of PIs on bone health in treatment experienced patients is less robust, the SPIRAL-LIP study found a 0.01 g/cm 2 increase in the femoral neck BMD of virologically suppressed patients switched from a PI/r-based regimen to a RAL-based regimen, with no statistically significant difference in the total body or total hip BMD [43].…”
Section: The Bone Effects Of the Hiv Protease Inhibitorsmentioning
confidence: 99%
“…In multivariate analysis, the loss of BMD at 96 weeks in patients treated with lopinavir/ritonavir was greater (by 2% in trunk and 1.3% in total body) than the loss observed in atazanavir/ritonavir‐treated patients. These investigators also observed a faster decline in BMD among older aged patients on these PI‐based regimens, with a 0.2% loss of total body BMD for every additional year of age . TDF in particular has been independently associated with a significant decrease in BMD at the hip (OR 2.8, 95% CI 1.3–5.9) and at the lumbar spine (OR 2.4, 95% CI 1.2–4.9) …”
Section: Toxicitymentioning
confidence: 82%
“…Mean BMD changes in the spine were −3.8% versus −1.8%, respectively (p<0.001), and changes in the hip were −3.7% versus −2.4%, respectively (p=0.005) . Another group compared BMD changes from baseline to week 96 of treatment with a combination of TDF/emtricitabine plus either atazanavir/ritonavir or lopinavir/ritonavir. In multivariate analysis, the loss of BMD at 96 weeks in patients treated with lopinavir/ritonavir was greater (by 2% in trunk and 1.3% in total body) than the loss observed in atazanavir/ritonavir‐treated patients.…”
Section: Toxicitymentioning
confidence: 99%
“…Low nadir CD4 cell counts have been associated with larger declines in BMD [62]. It is probable that HIV-related immune activation may also be a causative factor, with cytokines such as OPG and RANKL (associated with osteoclast activation and bone resorption) being present at higher concentrations in untreated HIV-infected patients compared to those with treated HIV or non-HIV-infected controls [63].…”
Section: Tolerability and Toxicitymentioning
confidence: 99%